Stagnation of Subnational Diplomacy in the Hometown of the President: A Critique of Local Leadership and the International Role of Pacitan Regency - Wisnu Wardhana, Riza Wildansyah; Hanggarini, Peni (CV. Era Digital Nusantara, 2025)
The involvement of national political figures in local governance often creates a dual dynamic in efforts to develop subnational diplomacy. Pacitan Regency, known for its close ties to a former president of the Republic of Indonesia originating from the region, is led by a local head of government who remains affiliated with elite national networks. This presents an illustrative case of limitations in leveraging international cooperation opportunities, such as the lack of formal sister city partnerships, minimal participation in global forums, and the absence of targeted strategies to attract foreign collaboration. Despite holding strong symbolic value, the region has yet to demonstrates success in building meaningful international partnerships. This study examines the condition of Pacitan’s subnational diplomacy by analyzing local political influence, symbolic power structures, and the interaction between local government and global actors. Using a qualitative approach and literature review, this article demonstrates that political symbolism, when not followed by institutional performance, tends to weaken a region’s diplomatic capacity. Dependence on symbolic status leads to a neglect of potential international cooperation and minimal public engagement in diplomacy.